METHODOLOGY FOR THE USE OF MODERN EDUCATIONAL TECHNOLOGIES IN RUSSIAN LANGUAGE LESSONS - M.Jurayeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
At the heart of modern education is the activities of the teacher. In the system of primary education, the science of the Russian language occupies a central place. It was thought about various pedagogical methods and forms that develop the knowledge skills of the Russian language of students.